Measuring Mainstream US Cultural Values - Doran, Caroline Josephine; Littrell, Romie Frederick (2013)
To determine and describe ‘mainstream US culture’ responses to the Schwartz Values Survey version 57 were collected and analyzed amongst two samples, one from 49 states, disregarding state of residence, and another from 27 US states comparing samples by state, with the 27-state populations representing about 82 % of the total US population. Statistical comparisons indicate that the responses of the samples categorised by the total US and state of residence samples and Schwartz’ ten individual cultural values show a cohesive mainstream US culture of the White, generally middle class population, having high motivational value priorities for self-direction, universalism and benevolence, with lowest priorities for power and achievement. We found significant value priority differences between urban and rural residents, but minimal differences relating to gender.
Keywords: Cultural areas; cultural values; American Culture; Schwartz Value Survey; Values